Analisa Perhitungan Pekerjaan Reparasi Kapal Dengan Metode Critical Path Method (CPM): cpm - Alamsyah bin Muh. Saleh Alam Muhammad (LPPM ITK, 2020)
Meranti Nusa Bahari carries out two types of businesses, firstly ship repair and secondly ship building services. Technical analysis of ship repair work using a simple table method. The purpose of this research is to find out how long the ship repairs. The method used is CPM (Critical Path Method). The results of this research are technical analysis of work using a simple table that is able to repair one unit of ship within 22 working days and 20 ships in a year. While the analysis with CPM method found 18 working days per unit of ship and 25 units of ships in a year. There has been a decrease in working time per ship unit of 4 working days which can be used to work on other vessels, with an increase in the number of vessels of 4 5 ships in a year where there is an increase in repair productivity by 20%.